1992
DOI: 10.1177/00220345920710010501
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlorhexidine Varnish Treatment on Salivary Mutans Streptococcal Levels in Child Orthodontic Patients

Abstract: A chlorhexidine dental varnish was applied to the teeth of 26 children, ten to 17 years of age, in an attempt to limit the increase in colonization by mutans streptococci that normally accompanies the placement of fixed orthodontic appliances and to assess the acceptance of the application procedure. Despite the insertion of the appliances in the month following the varnish application, the numbers of detectable salivary mutans streptococci in the children were found to remain significantly lower than baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 8 publications
0
26
0
5
Order By: Relevance
“…22,23 The number of oral bacteria can be reduced by brushing or by the additional use of fluoride, chlorhexidine, and antibiotics. [24][25][26] In addition, considerable effort has been made to produce antibacterial dental materials in oral environments.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The number of oral bacteria can be reduced by brushing or by the additional use of fluoride, chlorhexidine, and antibiotics. [24][25][26] In addition, considerable effort has been made to produce antibacterial dental materials in oral environments.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorzoin Âź was developed to achieve sustained release and, therefore, a long-term effect whilst minimising the known side effects of chlorhexidine [Balanyk and Sandham, 1985]. Initial reports indicated that this was indeed the case [Sandham et al, 1992]. This paper reports a randomised clinical trial with a primary aim of assessing the efficacy of a two-stage chlorhexidine varnish preparation, Chlorzoin [Sandham et al, 1992], in reducing the caries increment of high-caries-risk adolescents in Tayside, Scotland.…”
mentioning
confidence: 99%
“…It is known that the suppression of MS increases after repeated application of chlorhexidine varnish [Schaeken et al, 1989Petersson et al, 1991;Sandham et al, 1991;Ie and Schaeken, 1993;Twetman and Petersson, 1997]. Though, Sandham et al [1988Sandham et al [ , 1992 reported suppression of salivary MS from 1 to 6 weeks after a single application of 20% chlorhexidine varnish in all of the 27 treated patients. In the present study, a single application of a highly concentrated chlorhexidine varnish (40%) on top of the full dental treatment was performed in 11 children of the caries group.…”
Section: Discussionmentioning
confidence: 95%